Cognitive Psychology“The Effect of Cyberbullying on Anxiety Level and Learning Motivation” - Zahra Wirani (Psikologiya Journal, 2024)
The development of technology, especially the internet, has both positive and negative impacts on society. One of the negative impacts is the phenomenon of cyberbullying, which has increased especially during the Covid-19 pandemic. Cyberbullying, which often occurs on social media, can cause anxiety and decrease learning motivation in victims. The definition of cyberbullying is the act of humiliating, threatening or hurting someone online. Victims often feel anxiety due to the psychological pressure they experience. Anxiety is a feeling of fear of future events, and can affect a person's motivation to learn. Motivation to learn is influenced by the student's goals, abilities, conditions and environment. High anxiety is associated with low motivation to learn. Cognitive therapy is an effective approach to reduce the anxiety of bullying victims, focusing on controlling negative thoughts that arise as a result of bullying. Early treatment of bullying victims, including cognitive therapy, can help reduce anxiety levels and increase their motivation to learn.